Isn't that Feynman's paradox?

A circular disk with a radius R lies on a rough ground with coefficient of friction μ = μ 0 \mu ={ \mu }_{ 0 } .

Mass of the disk is non-uniform and the surface mass density as a function of the distance r from the center is given by σ = σ 0 ( 1 + r R ) \sigma ={ \sigma }_{ 0 }\left( 1+\frac { r }{ R } \right) .

The disk carries charge only in the region where the distance from the centre is r A r\ge A and the surface charge density of this region varies with r as ρ = α ( r A 1 ) \rho =\alpha \left( \frac { r }{ A } -1 \right)

A time varying magnetic field B = B 0 e n t B={ B }_{ 0 }{ e }^{ nt } exists in the region enclosed by the circle of radius A which is perpendicular to the plane of the disk and pointed into the screen.

If the disk starts rotating after a time t = ζ t=\zeta and if,

lim R ζ = 1 n [ ln ( ε σ 0 μ 0 g n α A B 0 ) ] \lim _{ R\rightarrow \infty }{ \zeta } =\frac { 1 }{ n } \left[ \ln { \left( \frac { \varepsilon { \sigma }_{ 0 }{ \mu }_{ 0 }g }{ n\alpha A{ B }_{ 0 } } \right) } \right] Then, ε = \varepsilon =

5/7 3/5 7/2 2/3 7/6

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Steven Chase
Aug 22, 2018

First, calculate the maximum possible friction torque, assuming that each infinitesimal ring of mass is supported by the surface directly underneath it. Here, d A d A will denote the infinitesimal ring area, and A A will denote the ring inner radius.

d A = 2 π r d r d m = σ d A = 2 π σ 0 ( r + r 2 R ) d r d F F = μ 0 d m g = 2 π μ 0 σ 0 g ( r + r 2 R ) d r d τ F = d F F r = 2 π μ 0 σ 0 g ( r 2 + r 3 R ) d r \large{d A = 2 \pi \, r \, dr \\ dm = \sigma \, dA = 2 \pi \, \sigma_0 \, \Big (r + \frac{r^2}{R} \Big) \, dr \\ dF_F = \mu_0 \, dm \, g = 2 \pi \, \mu_0 \sigma_0 \, g \, \Big (r + \frac{r^2}{R} \Big) \, dr \\ d \tau_F = dF_F \, r = 2 \pi \, \mu_0 \sigma_0 \, g \, \Big (r^2 + \frac{r^3}{R} \Big) \, dr }

Integrate to find the maximum possible total friction torque.

τ F = 2 π μ 0 σ 0 g 0 R ( r 2 + r 3 R ) d r = 2 π μ 0 σ 0 g ( R 3 3 + R 3 4 ) = 7 6 π μ 0 σ 0 g R 3 \large{ \tau_F = 2 \pi \, \mu_0 \sigma_0 \, g \, \int_0^R \Big (r^2 + \frac{r^3}{R} \Big) \, dr \\ = 2 \pi \, \mu_0 \sigma_0 \, g \Big( \frac{R^3}{3} + \frac{R^3}{4} \Big ) \\ = \frac{7}{6} \pi \, \mu_0 \sigma_0 \, g \, R^3 }

Next, determine the electric circular planar electric field, and corresponding electric torque. From the integral form of Faraday's Law of Induction:

2 π r E = B ˙ π A 2 E = B ˙ A 2 2 r \large{2 \pi \, r \, E = \dot{B} \, \pi \, A^2 \\ E = \frac{\dot{B} \, A^2}{2 r}}

Incorporating the infinitesimal charge element:

d Q = ρ d A = 2 π α ( r 2 A r ) d r d F E = d Q E = π α B ˙ A 2 r ( r 2 A r ) d r d τ E = d F E r = π α B ˙ A 2 ( r 2 A r ) d r \large{dQ = \rho \, d A = 2 \pi \, \alpha \, \Big( \frac{r^2}{A} - r \Big) \, dr \\ d F_E = dQ \, E = \frac{ \pi \, \alpha \, \dot{B} \, A^2}{r} \, \Big( \frac{r^2}{A} - r \Big) \, dr \\ d \tau_E = d F_E \, r = \pi \, \alpha \, \dot{B} \, A^2 \, \Big( \frac{r^2}{A} - r \Big) \, dr }

Total electric torque:

τ E = π α B ˙ A 2 A R ( r 2 A r ) d r = π α B ˙ A 2 ( R 3 3 A R 2 2 A 3 3 A + A 2 2 ) \large{\tau_E = \pi \, \alpha \, \dot{B} \, A^2 \, \int_A^R \Big( \frac{r^2}{A} - r \Big) \, dr \\ = \pi \, \alpha \, \dot{B} \, A^2 \, \Big (\frac{R^3}{3 A} - \frac{R^2}{2} - \frac{A^3}{3 A} + \frac{A^2}{2} \Big ) }

As R R tends toward infinity, the limit of the electric torque expression is:

τ E = π α B ˙ A R 3 3 \large{\tau_E =\frac{\pi \, \alpha \, \dot{B} \, A \, R^3}{3 } }

Setting the two torques equal:

7 6 π μ 0 σ 0 g R 3 = π α B ˙ A R 3 3 7 6 μ 0 σ 0 g = α B ˙ A 3 B ˙ = 7 μ 0 σ 0 g 2 α A \large{\frac{7}{6} \pi \, \mu_0 \sigma_0 \, g \, R^3 =\frac{\pi \, \alpha \, \dot{B} \, A \, R^3}{3 } \\ \frac{7}{6} \, \mu_0 \sigma_0 \, g =\frac{ \, \alpha \, \dot{B} \, A}{3 } \\ \dot{B} = \frac{7 \mu_0 \sigma_0 \, g}{2 \, \alpha \, A} }

Differentiating the B B expression and plugging in:

n B 0 e n t = 7 μ 0 σ 0 g 2 α A e n t = 7 μ 0 σ 0 g 2 α A n B 0 t = 1 n n ( 7 μ 0 σ 0 g 2 α A n B 0 ) \large{n \, B_0 \, e^{nt} = \frac{7 \mu_0 \sigma_0 \, g}{2 \, \alpha \, A} \\ e^{nt} = \frac{7 \mu_0 \sigma_0 \, g}{2 \, \alpha \, A \, n \, B_0} \\ t = \frac{1}{n} \, \ell n \Big( \frac{7 \mu_0 \sigma_0 \, g}{2 \, \alpha \, A \, n \, B_0} \Big)}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...